Tlingit man named Chief Charles Jones Shakes in front of new totem pole, Wrangell, Alaska, 1940. - University of Washington Libraries
Man wearing chilkat blanket and headpiece stands in front of painted totem pole, 1940. Same pole in NA3851 On verso of image: Pole designed and made by Tlingit carvers, CCC project supervised by U.S. Forest Service, Shakes Island. Dedicated June 1940 Note from unidentified source: Chief Shakes [Charles Jones Shakes] Wrangell, Alaska, standing in front of Gonaqadate pole on Shake's Island wearing Chilkat blanket with whales.